HT-B and S-RNase CRISPR-Cas9 double knockouts show enhanced self-fertility in diploid Solanum tuberosum - Lee, Sarah; Enciso-Rodriguez, Felix E.; Behling, William; Jayakody, Thilani; Panicucci, Kaela; Zarka, Daniel; Nadakuduti, Satya Swathi; Buell, C. Robin; Manrique-Carpintero, Norma C.; Douches, David S. (Frontiers in Plant Science, 2023)
The Gametophytic Self-Incompatibility (GSI) system in diploid potato (Solanum tuberosum L.) poses a substantial barrier in diploid potato breeding by hindering the generation of inbred lines. One solution is gene editing to generate self-compatible diploid potatoes which will allow for the generation of elite inbred lines with fixed favorable alleles and heterotic potential. The S-RNase and HT genes have been shown previously to contribute to GSI in the Solanaceae family and self-compatible S. tuberosum lines has been generated by knocking out S-RNase gene with CRISPR-Cas9 gene editing. This study employed CRISPR-Cas9 to knockout HT-B either individually or in concert with S-RNase in the diploid self-incompatible S. tuberosum clone DRH-195. Using mature seed formation from self-pollinated fruit as the defining characteristic of self-compatibility, HT-B-only knockouts produced little or no seed. In contrast, double knockout lines of HT-B and S-RNase displayed levels of seed production that were up to three times higher than observed in the S-RNase-only knockout, indicating a synergistic effect between HT-B and S-RNase in self-compatibility in diploid potato. This contrasts with compatible cross-pollinations, where S-RNase and HT-B did not have a significant effect on seed set. Contradictory to the traditional GSI model, self-incompatible lines displayed pollen tube growth reaching the ovary, yet ovules failed to develop into seeds indicating a potential late-acting self-incompatibility in DRH-195. Germplasm generated from this study will serve as a valuable resource for diploid potato breeding.